2020
DOI: 10.1016/j.jcte.2020.100233
|View full text |Cite
|
Sign up to set email alerts
|

1,5-anhydroglucitol is a good predictor for the treatment effect of the Sodium-Glucose cotransporter 2 inhibitor in Japanese patients with type 2 diabetes mellitus

Abstract: Highlights 1,5-AG is the novel predictor of HbA1c reduction with SGLT2 inhibitors. 1,5-AG is a useful predictor that is unaffected by the use of other diabetic drugs. The most appropriate 1,5-AG cutoff level is 7.65 µg/mL. In patients with 1,5-AG >7.7 µg/mL, SGLT2 inhibitors do not reduce HbA1c as much.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…We therefore investigated whether reduced 1,5-AG in HFD + E mice may contribute to increased cardiac glucose utilization by relieving inhibition of hexokinase. Consistent with previous reports regarding the effects of renal tubular glycemia on 1,5-AG levels in plasma [31][32][33], we found that cardiac concentrations of 1,5-AG were signi cantly reduced in HFD compared with LFD mice, and that 1,5-AG levels were also signi cantly reduced in HFD + E mice compared with both LFD and HFD mice (Fig. 7A; P < 0.0001).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We therefore investigated whether reduced 1,5-AG in HFD + E mice may contribute to increased cardiac glucose utilization by relieving inhibition of hexokinase. Consistent with previous reports regarding the effects of renal tubular glycemia on 1,5-AG levels in plasma [31][32][33], we found that cardiac concentrations of 1,5-AG were signi cantly reduced in HFD compared with LFD mice, and that 1,5-AG levels were also signi cantly reduced in HFD + E mice compared with both LFD and HFD mice (Fig. 7A; P < 0.0001).…”
Section: Resultssupporting
confidence: 92%
“…The metabolite 1,5-anhydroglucitol (1,5-AG) competes with glucose for reabsorption by the kidney such that SGLT2 inhibitor therapy, which raises renal tubular glucose concentrations, reduces plasma 1,5-AG levels by promoting 1,5-AG urinary excretion [31][32][33]. Phosphorylation of 1,5-AG produces 1,5-AG-6phosphate (1,5-AG-6P), which inhibits hexokinase and in turn glycolysis [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…It was proposed that such a reabsorption is competitively inhibited by glucose when glycemia exceeds the renal threshold for glucosuria (> 10 mmol/L), promoting 1,5-AG urinary excretion and lowering of its circulating levels (14). Of note, low blood 1,5-AG was identified as the most reliable indicator to identify T2D patients being responsive to treatment with SLC5A2/SGLT2 inhibitors and efficient HbA1c reduction, regardless of the estimated glomerular filtration rate (42). This is in line with our observation (ie, a close association between 1,5-AG levels and poor glucose control in patients with established T2D), although not in nondiabetic subjects.…”
Section: Discussionmentioning
confidence: 99%